THE EFFECT OF TECHNOLOGICAL INNOVATION ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN KENYA - WACHIRA, EVANGELINE; Ondigo, Mr. Herick (International Journal of Finance and Accounting, 2016)
Purpose: The present study endeavored to determine the effects of technological innovation on the performance of commercial banks in Kenya. Methodology: The study, which was a census, employed a descriptive cross sectional design and targeted all the commercial banks in Kenya. Secondary data in form of annual financial reports was obtained from Central Bank of Kenya. In addition, primary data was gathered from personnel from the customer care departments using a structured questionnaire. Data were analyzed using IBM SPSS Statistics 21.0 and involved computation of frequencies, descriptive statistics and multiple regression analysis. Results: Most of the respondents affirmed the positive impacts of technological innovations including ease of access, convenience, user friendliness among others. The study showed that customer care employees at the banks valued technological innovations. Moreover, the results revealed a positive and significant relationship between banks' performance in terms of profitability and adoption of various technological innovations including customer independent technology, customer assisted technology and customer transparent technology. The combined effect of the predictor variables (customer independent technology, customer assisted technology and customer transparent technology) was positively correlated with profitability (r=0.7) with 50.8% of the variations in profitability of banks in Kenya being explained by the model. Unique contribution to theory, practice and policy: The study underscored the need for banks to continuously invest in technological innovations for them to remain highly competitive